Linear dimerisation of terminal acetylenes using metal catalsts other than Cu2O and solvents other than glacial acetic acid - David, Angela Sharmini, author; Uraz, Inci, supervisor; Fakulti Sains (1986)
Project Paper (Sarjana Muda Sains serta Pendidikan) - Universiti Teknologi Malaysia, 1986